The Role of PT Pindad in Increasing Economic Growth - Rodiyah, Siti; Saputro, Guntur Eko; Suwito, Suwito (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2025)
The role of PT Pindad in the national economy is often overlooked and considered to only contribute to the defense sector. However, PT Pindad has greater potential as a locomotive of the country’s economy. The purpose of this study is to analyze the role of PT Pindad in increasing economic growth in Indonesia based on Biddle & Thomas’ role theory including Role Behavior, Role Conflict and Role Ambiguity. This research method is a qualitative description using literature review. The results showed that PT Pindad plays an important role in increasing national economic growth and other industrial sectors. There are complex dynamics in PT Pindad’s role behavior such as role conflict between business and defense missions. Role ambiguity arises due to dependence on government budgets. To achieve the independence of Indonesia’s defense industry, it is recommended that the government focus more on encouraging PT Pindad’s market expansion globally.